Cefalometria em crianças e adolescentes com história de exposição ao álcool durante a gestação - Vieira, Stella Maria Coda Pinto Alves Campos (2007)
Alcohol consumption during pregnancy is associated with a wide range of effects on birth, from which fetal alcohol syndrome is considered to lead to the most severe phenotypes. The teratogenic effects of alcohol on the human growth represent a spectrum of features on facial anomalies, growth deficiency at intrauterine into postnatal period, attention deficits and poor academic achievements. The aim of the present investigation was to study cephalometry as a diagnostic tool concerning craniofacial disorders in children and adolescents with confirmed mothers' alcohol intake history during the pre natal period. The specific objective was to analyse McNamara and Björk-Jarabak craniofacial parameters of ten children and adolescents who were exposed to alcohol during their mothers' pregnancy. The age of the subjects ranged from 11 to 18 years old, 5 were female. It was measured linear and angular variables compared to previous standards as descrived by McNamara and Björk-Jarabak. For this purpose, five linear measures and four angular parameters were taken into account in order to better describe craniofacial growth changes: maxilla length, mandibular length, anterior facial height, anterior cranial base, posterior cranial base, saddle angle, articular angle, gonial angle, upper gonial angle. Posterior cranial base, anterior facial height, mandibular size and tegumentary profile parameters were analysed as a whole in order to undertake global craniofacial development. The study showed that ten children and adolescents who were exposed to alcohol during their mothers' pregnancy were associated with linear measurements changes relative to posterior cranial base (p=0.01), mandibular size (p= 0.0009), face height (p= 0.01) and upper gonial angle (p= 0.01).